Ethnomathematics Study: Making Oncong-Oncong In Lembah Melintang District, West Pasaman - Ilhamdi Jobna; Ella Andhany (Journal of Innovation in Research, Education and Culture (JIREC), 2026)
This research aims to examine the mathematical concepts in the process of making oncong-oncong cakes. Oncong-oncong cake is one of the traditional foods from Indonesia that is still maintained to this day as a food ingredient that has ethnomathematical elements to its manufacture which is packaged using natural leaves in the shape of a cone. The purpose of this research was to examine the mathematical concept of making the oncong-oncong cake. So that the mathematical concepts found in the process of making this oncong-oncong cake can be used as an approach in mathematics learning activities. This research includes qualitative descriptive research with an ethnographic approach by means of interviews, observations, documentation, as well as the physical form of the product, packaging materials, and processing techniques used. The results of the study show that the use of leaves as packaging provides a protective function, maintains taste, and reflects local wisdom in the use of natural materials that are environmentally friendly. The shape of the cone also has aesthetic value and becomes a visual identity that distinguishes the product from similar foods. In addition to food sources, these traditional foods have the potential to be developed as part of cultural preservation and local economic strengthening. This research is expected to be a reference in the documentation and development of traditional foods based on local wisdom.